SmartGuard: an IoT-based intrusion detection system for smart homes. (26th June 2020) - Kesswani, Nishtha; Agarwal, Basant
With the help of sensor-enabled devices, we are able to achieve many tasks without human intervention. The sensor enabled internet of things has made our lives simple. But at the same time, security is an important issue that needs consideration. In this paper, we present an intrusion detection system, SmartGuard that can be deployed in the modern world's smart home. The system would be able to detect malicious behaviour within the network as well as any malicious communications from outside. In order to reduce the overhead on the energy constrained IoT devices, a cluster-based approach has been given and evaluated theoretically.